Persepsi kegunaan pengelolaan arsip digital menggunakan SIKD (sistem informasi kearsipan dinamis) - Fitriana Tjiptasari (Jurnal Kajian Informasi dan Perpustakaan, 2017)
The development of information technology has provided many changes in all aspects of online and offline life. This development requires the readiness of all lines to adjust to the needs of the changes, which are to support the realization of good government administration and the improvement of the quality of public services. This study aimed to determine the perceived usefulness of digital archive management using Dinamic Filing Information Systems (SIKD). The study used a descriptive quantitative approach. Data collection technique used questionnaires and was measured using the Likert scale. The instrument validity test used logical validity with expert judgment; reliability was measured using the Alpha Cronbach formula with coefficient value 0.796. Subjects of the study were a total of 19 educational staff of the Faculty of Education Yogyakarta State University. The result revealed that 78.9% of respondents claimed that Dinamic Filing Information Systems (SIKD) improved their performance. 94.8% of respondents stated that SIKD improved user productivity, and all respondents acknowledged that their perfomance increased due to the use of SIKD. Thus, SIKD provides the performance of an archive information system which is useful for archive management in Faculty of Education Yogyakarta State University and users are satisfied with this SIKD.